The Studies Of Ability To Cultivate Bananas In Protected And Coverless Conditions (Latakia University Journal -Biological Sciences Series, 2021)
The Research Aims To Study The Ability For Cultivating Bananas In Protected And Coverless Conditions .                             It Contains Many Major Topics : First Of All The Marketing Ability Which Depends On Growing Requirement For Bananas All Over The Year .                                                                     Second One Is The Social Ability Which Provides The Chance To Work In Agriculture , Transfer The Bananas And Distribution Them .                                                                         Third One Is The Environmental Ability That Considers Bananas Are Useful For Nature And They Give It A beautiful View And They Don’t Pollute It .                                                      Fourth One Is The Financial Ability Which Is Throughout The Government Supporting . Finally The Economical Ability Which Is The Basic One Because It Includes Calculation Processes To Build A Plastic Hole Which Its Size Is 1100 Square Meters , Its Running Costs And Its Economical And Financial Results . In Total This Research Studies How Much Money Does This Trilogy Plastic Hole Cost To Cultivate Bananas Throughout Three Basic Steps .Firstly : The Costs Of Building This Hole Is 15080000 Syrian Pounds According To The Agricultural Research Center InTartous Which Contains A Modify In Prices To Suitable These Days .Secondly : The Agriculture Costs Prove Than One kg Of Bananas Need At Most 707 Syrian Pounds , Were As The Price Of Bananas It 1600 Syrian Pounds In 2020 .Thirdly : In The Economical Calendar Which Does The Calculation Of Economical Indictors To Cultivate Bananas Inside The Protected And Coverless Conditions And Compare It With Its Similarities Of Other Agricultures .The Protected Conditions Consider That The Bananas Cultivation Has More Economical Efficiency Than Tomato Cultivation .The Coverless Conditions Prove That The Bananas Cultivation Has More Economical Efficiency More Than Citrus Fruits .      This Shows The Importance Of Revive This Agriculture Because It Has An Economical Necessary Through Providing Its Needs Of Different Materials , Protect It Of Its External Rivalry And Support Its Finance .